Diversity in the Workplace - Morgan, John; Várdy, Felix (American Economic Review, 2009)
We study minority representation in the workplace when employers engage in optimal sequential search and minorities convey noisier signals of ability than mainstream job candidates. The greater signal noise makes it harder for minorities to change employers' prior beliefs. When employers are selective, this leads to minority underrepresentation in the workplace. Diversity improves when the cost of interviewing, the average skill level of candidates, or the opportunity cost of not hiring increases. Reducing the cost of firing also increases minority representation. When employers are sufficiently unselective, the rigidity of employers' beliefs leads to overrepresentation of minorities. (JEL D83, J15, J24, J71, M12, M51)